Global health benefits associated with a substantial decrease in land transportation emissions during the COVID-19 period - Zhao, Yilong; Chen, Yubao; Zhuo, Fengqing; Fu, Hongbo (Frontiers in Environmental Science, 2024)
The changes in global air pollutant concentrations influenced by the COVID-19 lockdown have been widely investigated. The lack of clarity regarding the individual contributions to restricted human activities (i.e., transportation) has limited the understanding of the health impacts of the lockdown. In this study, an efficient chemical transport model (GEOS-Chem) was employed to simulate the concentration changes in air pollutants (PM2.5, NO2, and O3) associated with emission reductions in land transportation and the corresponding health benefits. The simulated results suggested that transportation-related PM2.5, NO2, and O3 reduced by 20%, 36%, and 55%, respectively. The reduction in O3 concentrations presented regional variations, with percentages ranked as follows: China (67%) > India (56%) > Europe (−81%) > the US (−86%), indicating the various intensities of secondary transformations with spatial relevance. The health benefits were also simulated, and the all-caused mortalities were estimated to be 63,547 (95% CI: 47,597, 79,497), 52,685 (95% CI: 32,310, 73,059), and 231,980 (95% CI: 210,373, 253,586) for the reduced concentration of PM2.5, NO2, and O3 globally, respectively. Transportation-related O3 reduction contributed the largest proportion (∼67%) to global health benefits, further emphasizing the global relevance and severity of O3 pollution. Our study confirms that the health benefits of transportation emission reduction during the COVID-19 lockdown were considerable and provides relevant simulated data as supporting evidence. We suggest that further coordinated efforts to restrict certain pollutants worldwide should focus on controlling the global O3 concentrations to protect people from severe O3 exposure.